DYNAMICS OF CHANGES IN ALGAE STRUCTURES AND COMPARISONS WITH OTHER RESERVOIRS - Mustafaeva Mamlakat Ismailovna; Sagdullayeva Gulandom Ulyanovna (Лучшие интеллектуальные исследования, 2024)
Resume: The article presents data on the comparative analysis of biological ponds, sewage treatment plants, which according to its climatic , hydrological and physical- chemical conditions of the environment is different from the other ponds. This article discusses the ecological- floral analysis of natural population of algal ponds used as biological ponds - reservoirs, clarifiers.